Correlation between the Finnish Diabetes risk Score and the severity of coronary artery disease - Đurić, Predrag; Mladenović, Zorica; Grdinić, Aleksandra; Tavčiovski, Dragan; Jović, Zoran; Spasić, Marijan; Davičević-Elez, Žaklina (Vojnosanitetski pregled, 2014)
Background/Aim. The FINish Diabetes RIsk SCore (FINDRISC) which includes age, body mass index (BMI), waist circumference, physical (in) activity, diet, arterial hypertension, history of high glucose levels, and family history of diabetes, is of a great significance in identifying patients with impaired glucose tolerance and a 10-year risk assessment of developing type 2 diabetes in adults. Due to the fact that the FINDRISC score includes parameters which are risk factors for coronary artery disease (CAD), our aim was to determine a correlation between this score, and some of its parameters respectively, with the severity of angiographically verified CAD in patients with stable angina in two ways: according to the Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) score and the number of diseased coronary arteries. Methods. The study included 70 patients with stable angina consecutively admitted to the Clinic of Cardiology, Military Medical Academy, Belgrade. The FINDRISC score was calculated in all the patients immediately prior to angiography. Venous blood samples were collected and inflammatory markers [erythrocyte sedimentation rate (ESR), leucocytes, C-reactive protein (CRP), total cholesterol, HDL cholesterol, triglycerides and fasting glucose] determined. Coronary angiography was performed in order to determine the severity of coronary artery disease according to the SYNTAX score and the number of affected coronary vessels: 1-vessel, 2-vessel or 3-vessel disease (hemodynamically significant stenoses: more than 70% of the blood vessel lumen). The patients were divided into three groups regarding the FINDRISC score: group I: 5-11 points; group II: 12–16 points; group III: 17–22 points. Results. Out of 70 patients (52 men and 18 women) enrolled in this study, 14 had normal coronary angiogram. There was a statistically significant positive correlation between the FINDRISC score and its parameters respectively (age, body mass index-BMI, waist circumference) and the severity of CAD according to the SYNTAX score (p < 0.001) and the number of diseased coronary arteries (p < 0.001). The patients with higher FINDRISC score (groups II and III) had more severe and extensive CAD according to the SYNTAX score than the group I. The odds ratio with 95% confidence intervals (CI) between the group III and the group I was 5.143 (95% CI 1.299–20.360, p = 0.002) and between the group II and the group I 5.867 (95% CI 1.590–21.525, p = 0.007). There were no differences in odds ratio for multivessel disease according to FINDRISC score between the group II and the group III [1.141; (95% CI 0.348–3.734). In the group I mean SYNTAX score was 5.18, and more than 70% of patients had normal coronary angiogram. In the group II mean SYNTAX score was 17.06, and more than 70% of patients had 2-vessel disease and 3-vessel disease, and in the group III mean SYNTAX score was 18.89, and 2-vessel and 3-vessel disease had 36.36% and 31.82% patients, respectively. In multiple regression analysis, where SYNTAX score was dependent variable, and age, BMI, waist circumference, FINDRISC score were independent variables, we found that only FINDRISC score was independent predictor of SYNTAX score. Conclusion. The obtained results suggest a statistically significant correlation between the FINDRISC score and its parameters (age, BMI, waist circumference) and the severity of CAD according to the SYNTAX score and the number of diseased coronary arteries. The FINDRISC score may be useful in identifying patients at the high risk for coronary artery disease.